Synthesis And Characterization Of Acid-Activated Sago Dregs Biochar And Testing Its Ability As An Adsorbent For Rhodamine B Dyes - Ariyani, Dahlena (Jurnal Sains dan Terapan Kimia, 2025)
Synthesis & characterization of acid-activated sago pulp biochar as an adsorbent of rhodamine B dye has been carried out. This study aims to synthesize & characterize sago pulp biochar activated with HCl 1 M & H3PO4 0,214 M solutions & to assess its ability as an adsorbent of rhodamine B dye. This biochar is produced through a pyrolysis method with a combustion temperature of 700 °C for 2 hours. The results of the pyrolysis biochar were then activated with HCl 1 M & H3PO4 0,214 M acid solvents & then analyzed the effect of contact time, pH, & initial concentration on its ability to adsorb rhodamine B dye. Characterization using Fourier Infrared (FTIR) showed the presence of alkene groups & aromatic groups (C=C) & bonds (CO) & (CC) which play an important role in the adsorption process. The results of the water content of BAS, BAS/HCl & BAS/H3PO4 produced were 2.57%, 4.47% & 5.06% which met the requirements of SNI 06-3730-1995. The results of the surface area test showed BAS/H3PO4 with the largest surface area of 0,520 m2/g & BAS of 0,452 m2/g while the smallest surface area was BAS/HCl of 0,445 m2/g. The study of the effect of pH & contact time on the adsorption capacity of rhodamine B showed that the optimum adsorption capacity of pure sago pulp biochar (BAS) at neutral pH with a contact time of 15 minutes, BAS/HCl at acidic pH with a contact time of 180 minutes, & BAS/H3PO4 at alkaline pH with a contact time of 60 minutes. Based on the analysis results, the adsorption process of rhodamine B on biochar follows the Langmuir & Freundlich isotherms with maximum adsorption capacities for BAS, BAS/HCl, & BAS/H3PO4 of 4.285 mg/g, 4.834 mg/g, & 3.934 mg/g, respectively.